Liquid Chromatography–Mass Spectrometry in the Development of Natural Product–Based Antihypertensive Drugs: A Systematic Literature Review - Nur Pujiastuti; Novi Yantih; Ridel Yosua Rumondor; Kholilah (Journal of Natural Product for Degenerative Diseases, 2026)
Hypertension remains a major global health burden, necessitating effective and evidence-based therapeutic strategies. Natural products have emerged as promising sources of antihypertensive agents; however, their chemical complexity requires advanced analytical techniques such as liquid chromatography–mass spectrometry (LC–MS). This study employed a systematic literature review of articles published between 2020 and 2025, retrieved from Scopus, PubMed, and ScienceDirect using predefined inclusion criteria. The review evaluates the application of LC–MS in the identification, metabolite profiling, and standardization of antihypertensive natural products, with emphasis on celery (Apium graveolens). The findings indicate that LC–MS enables accurate identification of key bioactive compounds, including flavonoids, phenolic acids, alkaloids, and phthalides, which are associated with antihypertensive mechanisms such as angiotensin-converting enzyme (ACE) inhibition, vasodilation, and endothelial protection. Integration with pharmacological and in silico approaches further supports the correlation between chemical composition and biological activity. In conclusion, LC–MS is a critical tool in natural product-based antihypertensive drug discovery, particularly for compound characterization and standardization. However, lack of standardized workflows remains a limitation for reproducibility and clinical translation.